IMPLEMENTASI MODEL CHALLENGE BASED LEARNING TERHADAP PENINGKATAN LITERASI NUMERASI PESERTA DIDIK - Karmelia; Nurjanah, Rina Siti (Universitas Islam Nusantara, 2025)
This research is motivated by the low numeracy literacy skills experienced by students, so a relevant learning model is needed tosolve this problem, one of which is the Challenge-Based Learning model. The study aimed to analyze the differences in theaverage increase in numeracy literacy skills between students using the Challenge-Based Learning model and students using theDiscovery Learning model. This research is a quantitative study that examines a causal correlation. The research was conducted atone of the MTs in West Bandung Regency. The sample for this research consisted of students from classes VIII A and VIII B. Theinstruments used in this study were tests of numeracy literacy skills. The results showed that there was a difference in theaverage increase in numeracy literacy skills between students who used the Challenge-Based Learning model and students whoused the Discovery Learning model.